2014
DOI: 10.1073/pnas.1321195111
|View full text |Cite
|
Sign up to set email alerts
|

Paternally induced transgenerational inheritance of susceptibility to diabetes in mammals

Abstract: The global prevalence of prediabetes and type 2 diabetes (T2D) is increasing, and it is contributing to the susceptibility to diabetes and its related epidemic in offspring. Although the impacts of paternal impaired fasting blood glucose and glucose intolerance on the metabolism of offspring have been well established, the exact molecular and mechanistic basis that mediates these impacts remains largely unclear. Here we show that paternal prediabetes increases the susceptibility to diabetes in offspring throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
345
2
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(367 citation statements)
references
References 35 publications
12
345
2
8
Order By: Relevance
“…Induction of a pre-diabetic state in fathers (feeding a high fat diet in combination with streptozotocin injection) altered pancreatic gene expression pattern in male offspring. 26 In our study, we detected altered gene expression in the liver of HFD male offspring compared to LFD male offspring. Several of the differentially expressed genes play a role in lipid metabolism (Acaca, Fasn, Por, and Sqle) and are involved in the oxidative-reduction pathway (Mt1, Mt2, Por, and Sqle).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Induction of a pre-diabetic state in fathers (feeding a high fat diet in combination with streptozotocin injection) altered pancreatic gene expression pattern in male offspring. 26 In our study, we detected altered gene expression in the liver of HFD male offspring compared to LFD male offspring. Several of the differentially expressed genes play a role in lipid metabolism (Acaca, Fasn, Por, and Sqle) and are involved in the oxidative-reduction pathway (Mt1, Mt2, Por, and Sqle).…”
Section: Discussionmentioning
confidence: 57%
“…24,25 A number of studies have reported that a parental diet containing high fat or imposing calorie restriction modulates the phenotype of the offspring. [26][27][28] Under-nourishment in utero leads to methylome changes in the sperm of the male progeny and metabolic changes that are inherited to the subsequent generation. 29 A high fat paternal diet in rodents changes the insulin and glucose levels in offspring serum and induces an abnormal response after glucose or insulin injections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows that much of our knowledge of transgenerational epigenetic inheritance in mammals pertains largely to inbred mice, where maternally or paternally induced transmission can come in the form of covalent modifications to DNA and histone methylation (e.g. Padmanabhan et al 2013;Wei et al 2014;Siklenka et al 2015) and altered RNA expression (Wagner et al 2008), often in a breeding scheme-dependent manner (Yuan et al 2015). Not surprisingly, evidence for similar effects occurring in long-lived and out-bred farm animals is scarce, leading González-Recio et al (2015) to question its importance in livestock production.…”
Section: Inter(trans)generational Inheritancementioning
confidence: 99%
“…Epigenetic inheritance has been demonstrated in several species including worm (2), fly (3) and mouse species (4,5). Epigenetic inheritance can be modulated by environmental factors and transmitted to subsequent generations via germline cells (6,7). …”
Section: Introductionmentioning
confidence: 99%